2005
DOI: 10.1111/j.1365-2443.2005.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of γ‐secretase by truncated presenilin (PS) fragments revealed that PS C‐terminal transmembrane domain is critical for formation of γ‐secretase complex

Abstract: The presenilin (PS) complex, including PS, nicastrin (NCT), APH-1 and PEN-2, is essential for γ γ γ γ -secretase activity. Previously, the PS C-terminal tail was shown to be essential for γ γ γ γ -secretase activity. Here, to further understand the precise mechanism underlying the activation of γ γ γ γ -secretase regulated by PS cofactors, we focused on the role of the PS1 C-terminal region including transmembrane domain (TM) 8 in γ γ γ γ -secretase activity. For this purpose, we co-expressed Cterminally trunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
(81 reference statements)
0
7
1
Order By: Relevance
“…In the case of APH-1, our siRNA targeted APH-1αL because it has been suggested to be the dominant form of APH-1. However, recent studies report that multiple isoforms (αL, αS, and β) of APH-1 can replace each other in the γ-secretase complex (35, 36), and this may provide an explanation why our siRNA against APH-1 has less of an effect on γ-secretase activity. It has been shown that PS1 knockdown leads to a strong reduction of PEN-2 and that the PEN-2 level is also down-regulated upon siRNA knockdown of nicastrin (37).…”
Section: Discussionmentioning
confidence: 90%
“…In the case of APH-1, our siRNA targeted APH-1αL because it has been suggested to be the dominant form of APH-1. However, recent studies report that multiple isoforms (αL, αS, and β) of APH-1 can replace each other in the γ-secretase complex (35, 36), and this may provide an explanation why our siRNA against APH-1 has less of an effect on γ-secretase activity. It has been shown that PS1 knockdown leads to a strong reduction of PEN-2 and that the PEN-2 level is also down-regulated upon siRNA knockdown of nicastrin (37).…”
Section: Discussionmentioning
confidence: 90%
“…Co-immunoprecipitation-Co-immunoprecipitation was carried out based on Shiraishi et al (44) and Xia et al (55). 48 h after transfection, CHO cells were washed with cold PBS and homogenized in lysis buffer A (50 mM Tris, pH 7.6, 150 mM NaCl, 2 mM EDTA, 1% CHAPS, and protease inhibitor mixture).…”
Section: Methodsmentioning
confidence: 99%
“…This domain is involved in the formation and stability of the complex (44,45) and in the membrane integration of TMD7 into the membrane bilayer by "forced transmembrane orientation" (43). In PS1, both motifs include two critical amino acids: Gly-417, having a pivotal role in ␥-secretase activity (46), and Ala-409, whose substitution with Thr (PS1 A409T) is described as a FAD mutation (47).…”
Section: A␤mentioning
confidence: 99%
“…In healthy individuals, most of the APP is constitutively cleaved within the Aβ sequence by α‐secretase enzymes (TACE/ADAM17 and/or ADAM10) generating the soluble ectodomain of APP (sAPPα) and a truncated C‐terminal peptide (CTF‐α or C‐83). In the amyloidogenic pathway, APP is proteolyzed by β‐secretase (BACE‐1) forming the smaller membrane bound C‐terminal fragment (CTF‐β or C‐99), which is further cleaved by the γ‐secretase leading to Aβ formation (Cai et al, ; De Strooper, ; De Strooper and Annaert, ; Glenner and Wong, ; Iwatsubo, ; Shiraishi et al, ; Vassar et al, ).…”
Section: Introductionmentioning
confidence: 99%